SOME IMPLEMENTATION PROBLEMS INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2006)
This article is devoted to the basical organizational problems of for mulation electronic information trends in educational process.